2012
DOI: 10.1002/jssc.201200332
|View full text |Cite
|
Sign up to set email alerts
|

Determination of L‐trantinterol in rat plasma by using chiral liquid chromatography‐tandem mass spectrometry

Abstract: A simple, sensitive, and rapid method for determination of L-trantinterol in rat plasma was developed for the first time by using LC coupled to MS/MS based on chiral stationary phase. A baseline separation of the enantiomers of trantinterol was achieved on a Chirobiotic V column, using a mixture of acetonitrile-methanol-ammonia-acetic acid (80:20:0.01:0.02, v/v/v/v) as the mobile phase. The detection was performed on a triple-quadrupole tandem mass spectrometer by multiple reaction monitoring mode via ESI. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, the chiral inversion of phenylethanolamine derivatives has not been documented. Our previous study found that a chiral inversion of trantinterol occurred to some extent in rats . The purpose of this article is to report our observation of substantial bidirectional chiral inversion after oral and intravenous administration of (−)‐ and (+)‐trantinterol to rats.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the chiral inversion of phenylethanolamine derivatives has not been documented. Our previous study found that a chiral inversion of trantinterol occurred to some extent in rats . The purpose of this article is to report our observation of substantial bidirectional chiral inversion after oral and intravenous administration of (−)‐ and (+)‐trantinterol to rats.…”
Section: Introductionmentioning
confidence: 89%
“…A previously validated stereospecific assay was modified. An aliquot of IS solution (100 μL) was pipetted into a 10‐mL glass tube and evaporated to dryness.…”
Section: Methodsmentioning
confidence: 99%
“…However, currently, only a handful of methods have been reported for the quantification of trantinterol in biological samples based on LC-MS/MS [9][10][11][12][13]. Furthermore, all the previous in vivo pharmacokinetics studies of trantinterol after oral administration had http://dx.doi.org/10.1016/j.jchromb.2015.07.022 1570-0232/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 96%
“…Few methods have been reported for the quantification of trantinterol in biological fluids [3][4][5]. And only one published literature reported a LC-MS/MS method [6] for the simultaneous determination of trantinterol and its major metabolites in rat urine and feces.…”
Section: Introductionmentioning
confidence: 98%